Rapid Diagnosis and Management of Concomitant Acute Cardiogenic Pulmonary Edema and Community-Acquired Pneumonia Increase Patient Survival - Wibowo, Adityo; Saputra, Tetra Arya (Medula, 2024)
Acute pulmonary edema is a potentially life-threatening complication of cardiac disease that leads to acute respiratory failure. Cardiogenic pulmonary edema affects approximately 80% of patients with acute decompensated heart failure. Acute pulmonary edema caused by heart failure affects nearly a million individuals annually, and the number of cases is growing significantly as the ejection fraction reduces. The clinical presentation can be identified by a sudden onset of dyspnea and a quick accumulation of fluid inside the alveolar and lung interstitial secondary to an increase in hydrostatic pressure. Community-acquired pneumonia (CAP) is the most common respiratory infection caused by a microbial infection of the lung parenchyma and has almost similar clinical characteristics to acute pulmonary edema. The length of stay in hospital will increase nearly two times longer in these concomitant diseases. Comorbidity of cardiogenic lung edema and CAP increase mortality rate by nearly 25% in heart failure patients without early detection and proper management.